Breaking the Law: Is It Correct to Use the Converse Bergmann Rule in Ceroglossus chilensis? An Overview Using Geometric Morphometrics - Benitez, Hugo A.; Munoz-Ramirez, Carlos; Correa, Margarita; Acuna-Rodriguez, Ian S.; Villalobos-Leiva, Amado; Contador Mejias, Tamara Andrea; Velasquez, Nelson A.; Suazo, Manuel J. (My University, 2024)
The converse Bergmann's rule is a pattern of body size variation observed in many ectothermic organisms that contradicts the classic Bergmann's rule and suggests that individuals inhabiting warmer climates tend to exhibit larger body sizes compared to those inhabiting colder environments. Due to the thermoregulatory nature of Bergmann's rule, its application among ectotherms might prove to be more complicated, given that these organisms obtain heat by absorbing it from their habitat. The existence of this inverse pattern therefore challenges the prevailing notion that larger body size is universally advantageous in colder climates. Ceroglossus chilensis is a native Chilean beetle that has the largest latitudinal range of any species in the genus, from 34.3 degrees S to 47.8 degrees S. Within Chile, it continuously inhabits regions extending from Maule to Aysen, thriving on both native and non-native forest species. Beyond their remarkable color variation, populations of C. chilensis show minimal morphological disparity, noticeable only through advanced morphological techniques (geometric morphometrics). Based on both (1) the "temperature-size rule", which suggests that body size decreases with increasing temperature, and (2) the reduced resource availability in high-latitude environments that may lead to smaller body sizes, we predict that C. chilensis populations will follow the converse Bergmann's rule. Our results show a clear converse pattern to the normal Bergmann rule, where smaller centroid sizes were found to be measured in the specimens inhabiting the southern areas of Chile. Understanding the prevalence of the converse Bergmann's rule for ectotherm animals and how often this rule is broken is of utmost importance to understand the underlying mechanisms allowing organisms to adapt to different environments and the selective pressures they face.
Keywords: converse bergmann's rule; centroid size; carabidae; geometric morphometrics; body size; sexual dimorphism